Midstream Supply Chain Infrastructure Facilities and Optimization Opportunities for Emerging LNG Markets - El Ghazi, Firdaous; Lechheb, Charafeddine; Kaitouni, Omar Drissi (International Journal of Energy Economics and Policy, 2023)
Liquified Natural Gas (LNG) is a major energy market experiencing significant supply chain evolution. Supply terms are progressively changing from long-term and binding contracts to shorter-term and flexible clauses, taking into consideration demand uncertainties. This context is making heavy investments in the LNG infrastructure risky, costly, and irreversible. The focus is shifting towards small-scale midstream facilities to develop small-size markets. This paper presents a comprehensive analysis of the LNG supply chain from an infrastructure investment approach based on market size and recent technological developments in the field. It addresses the limitations of the classic conducted supply chain and investigates best practices adapted to emerging markets. If properly executed, these logistics alternatives enable emerging markets to access LNG in a short period with lower investment. The objective is to maximize added value while minimizing cost and operational risks. This work suggests an alternative supply chain process replacing onshore terminals and pipeline delivery by Floating Storage Regasification Unit (FRSU) and truck delivery in the midstream market. A SWOT analysis is conducted for the alternative supply chain model, showcasing the strengths and weaknesses alongside opportunities and threats. The result and discussion section develop the main aspects of strategic and operational supply chain decision-making for LNG to find new developing opportunities and faster growth.